1996
DOI: 10.1007/bf02246018
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of buprenorphine and a nondrug alternative reinforcer on IV cocaine self-administration in rats maintained under FR schedules

Abstract: Although previous studies have shown that pharmacological agents, such as buprenorphine, and alternative nondrug reinforcers, such as money or sweetened solutions, reduce cocaine self-administration, few studies have examined the combined effects of these two approaches. The purpose of the present study was to evaluate the effects of the opioid partial against buprenorphine (0.1 mg/kg) and concurrent access to either water or a glucose plus saccharin solution (G+S, 3% and 0.125% wt/vol) in rats self-administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
40
1

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 22 publications
6
40
1
Order By: Relevance
“…Similarly, in the PR procedure, supplying food returned the elevated break point to normal in LgA rats but had no consequence in ShA rats. As a whole, these observations clearly showed that food consumption can act as a potent substitute for heroin use in individuals that have escalated their heroin use, confirming and extending to heroin intake escalation previous research on other drugs of abuse (Carroll et al, 1991(Carroll et al, , 1995Comer et al, 1996;Carroll, 1996, 1997).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similarly, in the PR procedure, supplying food returned the elevated break point to normal in LgA rats but had no consequence in ShA rats. As a whole, these observations clearly showed that food consumption can act as a potent substitute for heroin use in individuals that have escalated their heroin use, confirming and extending to heroin intake escalation previous research on other drugs of abuse (Carroll et al, 1991(Carroll et al, , 1995Comer et al, 1996;Carroll, 1996, 1997).…”
Section: Discussionsupporting
confidence: 81%
“…As with the consumption of nondrug reinforcers, the consumption of drugs (eg ethanol, phencyclidine, cocaine, heroin) decreases in the face of increasing prices in both rats (eg Comer et al, 1996;Solinas et al, 2004;Heyman et al, 1999) and monkeys (Carroll et al, 1991;Carroll, 1996, 1997;Ko et al, 2002) (for a general review, Bickel et al, 1995). In the majority of studies, the demand for drug is initially inelastic to changes in price and then becomes elastic above a certain price, called P max (Hursh, 1991;Bickel et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon parallels the enhancement, by food restriction, of drug self-administration (Carroll and Meisch 1984) and conditioned place preference (Bell et al 1997), and appears to reflect an increase in sensitivity of the neural substrate for drug reward (Cabeza de Vaca and Carr 1998). The augmentation of drug reward by food restriction is just one of numerous observations that support an association between drug-seeking and ingestive behavior (Sills et al 1998;Gosnell et al 1995;Comer et al 1996;Sills and Vaccarino 1994;Gosnell 2000). Although the physiological mechanisms underlying the augmentation of drug reward by food restriction have not been established, the augmented rewarding effect of amphetamine in food-restricted subjects is associated with increased cfos expression in limbic forebrain dopamine terminal areas (Carr and Kutchukhidze 2000).…”
Section: Introductionmentioning
confidence: 88%
“…One interesting phenomenon that may suggest common pathways for food consumption and drug use is that chronic food restriction increases food reinforcement (H. A. and also increases the self-administration and motor-activating effects of abused drugs (Carr, 2002;Carroll & Meisch, 1984;Pothos, Creese, & Hoebel, 1995), along with improving dopamine receptor function (Wilson, Nomikos, Collu, & Fibiger, 1995). In addition, an animal's level of sucrose preference can predict its desire to self-administer cocaine (Levine et al, 2003), and sweets will reduce cocaine's reinforcing value (Comer, Lac, Wyvell, & Carroll, 1996), suggesting a relation between sweet taste and drug reward. Both obese rats and chronic drug users have low basal dopamine levels (Hamdi, Porter, & Prasad, 1992), experience periodic exaggerated dopamine release associated with either food (Fetissov et al, 2002) or drug intake (Worsley et al, 2000), and have reduced dopamine D2 receptor and increased D1 receptor expression (Fetissov et al, 2002).…”
Section: Common Neurobiological Substrates For Obesity and Drug Addicmentioning
confidence: 99%